Audit Sistem Informasi Menajemen Puskesmas Menggunakan Cobit 5 Dengan Domain DSS (Deliver, Service and Support) - Ardiansyah, Reza; Sutabri, Tata (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
The Community Health Center Management Information System (SIMPUS) is used to provide services at the Community Health Center, from patient registration to medical services. There are several regulatory inconsistencies that occur, so an evaluation using COBIT 5 is needed to evaluate the level of capability (As-Is) and draw conclusions. Therefore, in this research, an information system audit will be carried out using the COBIT 5 Framework by measuring the Capability Level (maturity) and Gap Analysis (gap level analysis). The domains used are DSS02 (managing service requests and incidents) and DSS03 (problem management) to produce recommendations for improving the information system for existing problems. The audit results in this study show that the Capability Level for the entire domain is at the Largely Achieved criteria where the DSS02 domain is worth 3.73, DSS03 is worth 3.75, which means that the overall domain results are at level 3 (established process), which means that the system has been implemented and has been implemented. running but not yet optimally and already approaching maximum and there needs to be improvements to the SIMPUS system as well as monitoring the performance of human resources and the Puskesmas operational system in the future to get maximum results. The results of the gap level (Gap Analysis) in DSS02 are 1.27 and DSS03 are 1.25